LAPORAN KASUS: LOW GRADE FIBROMYXOID SARCOMA RECURRENT REGIO FEMUR SINISTRA - Gunawijaya, Anlidya Permatasari (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana, 2014)
I report a case of 42 years old man who presented with a huge tumor on left thigh that progressively growing in 10 months. This patient had history of three times tumor resections and local recurrent, but had not received any other therapy. Physical examination on left thigh region showed a mass with size 40x20x10 cm, solid, fixed, with ulcers and bleeding. Histological evaluation revealed a cellular lesion consist of spindle cells with atypical fibroblast in collagenous stroma, arranged in plexiform pattern. This patient was diagnosed with low grade fibromyxoid sarcoma recurrent regio femur sinistra and treated with wide excision.
Keywords: low grade fibromyxoid sarcoma, reccurent, wide excision